Dampak Implementasi Kurikulum Merdeka terhadap Kompetensi Literasi dan Numerasi Siswa Sekolah Dasar - Erlis Thertina; Ruben Edward; Jumadi Jepri (SAP (Susunan Artikel Pendidikan), 2025)
This study aims to analyse the impact of Merdeka Curriculum implementation on improving primary school students' literacy and numeracy competencies. The background of this research departs from the importance of literacy and numeracy as the main foundation in basic education and the urgency of evaluating the new curriculum policy being implemented in Indonesia. The research approach used was quantitative with a comparative study design. Data were collected through literacy and numeracy competency tests given to students before and after the implementation of Merdeka Curriculum, and supplemented with observations and questionnaires to teachers. The results showed a significant improvement in students' literacy and numeracy achievement, which was attributed to the implementation of differentiated learning strategies, Pancasila learner profile-based projects, and formative assessments. The findings are in line with constructivism theory and the competency-based curriculum underlying the Merdeka Curriculum policy. This research provides theoretical contributions to curriculum development as well as practical contributions for educators and policy makers in an effort to improve the quality of basic education in Indonesia.